Noise Pollution: Knowledge, Attitudes and Practice of Sawmill Workers in Osun State, Nigeria (Nigerian Journal of Health Sciences, 2023)
Background: Literature on awareness of the harmful effect of noise on the health, hearing, and the quality of life of Nigerians engaged in noisy occupation is scarce. Objective: The objective was to assess the knowledge, attitudes, and practice of  sawmill workers and owners to noise pollution; and the need for prevention with the use of hearing protection devices.Subjects and Methods: This was a purposive sampling of sawmills in 6 local government areas in Osun state. The respondents were studied using interviewer-administered questionnaires. The workplace noise levels were assessed.Results: A total of 412 male respondents, consisting of 400 sawmill workers and 12 sawmill owners were studied. The mean age of the respondents was 32 years. Average time of exposure to noise was 10 h/day. The average level of noise at the sawmills was 108 ± 9 dB. 140 (35.0%) sawmill workers could not identify the sources of noise correctly. 140 (85.0%) would endure noise exposure, and 376 (94.0%) did not know that hearing loss could be due to noise exposure. 176 (44.0%) of the workers believed that noise had no impact on health, while 373 (93.3%) did not believe that noise was associated with a change in productivity. None of the sawmill owners was familiar with policy on noise control and none of them provided earmuffs or plugs for their workers.Conclusion: Sawmill workers and their employers in the present study were not aware of the harmful effects of noise on their health. Hearing protection devices were therefore not available or worn by most sawmill workers. The sawmill workers were thus at risk of developing noise-induced hearing loss.